Upaya Perbaikan Kualitas pada Proses Pengemasan Kedelai di PT Sari Agrotama Persada Gresik Menggunakan Metode Failure Mode and Effect Analysis - Muhammad Firman Afandi; Deny Andesta; Yanuar Pandu Negoro (Jurnal Serambi Engineering, 2022)
PT Sari Agrotama Persada Gresik is an agribusiness company, and has been operating in Gresik since 2018 on soybean packaging, based on data from the company, where it is still found in their products, both from customer complaints and during the production process. Which is more directed at product packaging, it causes the quality required by the company, and product appearance has a big role in customer interest and trust. This study aims to determine the type, causative factors and recommendations for recommendations. In this study using Pareto diagrams to describe the level of product type, fishbone diagrams to find the factors of occurrence and FMEA (Failure Mode and Effect Analysis) methods to identify failure modes, determine failure effects and causes, assign severity, occurrence and detection values, calculating the Risk Priority Number (RPN). To do to find out the dominant factors causing the defect and provide an offer, then in the hope that it can be a consideration for companies to reduce or even eliminate their products, to produce products that comply with company standards.